Analysis of Scientific and Press Articles Related to Cultured Meat for a Better Understanding of Its Perception - Chriki, Sghaier; Ellies-Oury, Marie-Pierre; Fournier, Dominique; Liu, Jingjing; Hocquette, Jean-François (Frontiers in Psychology, 2020)
Cultured meat is presented by its advocates as a good alternative for consumers who want to be more ethically minded but who do not wish to change their diet. This novel food has been an emerging topic in both the scientific field and the press media. From a bibliometric analysis of scientific publications and on a sociometric analysis of the mainstream press, the aim of this study was to identify potential differences between the scientific view and the public perception. This research analysed the publications indexed by SCI-EXPANDED in the Web of Science Core Collection database owned by Clarivate Analytics, for scientific literature analysis, and indexed by the Factiva database, for the press media. A total of 327 scientific publications was analysed according to year of publication, country and institution of origin, also including co-authorships, co-citations, scientific fields’ and journals networks. A knowledge mapping using VOSviewer was used to study the literature in the field. Based on Factiva, 12,900 press articles dealing with artificial meat, mainly in English, have been found through public databases. The main conclusion is that cultured meat is mainly developing in the USA and the UK, with other countries, such as China observing the trend for potential future applications. Scientific articles seemed initially to focus mainly on technical aspects of artificial meat, and more recently on health value, consumer’s acceptance, and sustainability. However, the potential environmental-friendly effects of this novel food are more and more studied or described in scientific or press articles.